Hubungan Tingkat Stress Dengan Siklus Menstruasi pada Remaja Putri di MAN 2 Karanganyar - Anisa Putri Yuliana; Maryatun Maryatun (Lembaga Pengembangan Kinerja Dosen, 2024)
The problems of adolescents in the world are around problems regarding menstruation disorders (38.45%), nutritional problems related to anemia (20.3%), learning disorders (19.7%), psychological disorders (0.7%), and obesity problems (0.5%). Abnormal menstruation cycles can cause mental-emotional disturbances (depression and anxiety) in as many as 9.8% of people over 15 years of age in Indonesia. Several factors alter the menstrual cycle including phytoestrogen intake and level of sexual activity. Purpose; to determine the level of stress on the menstruation cycle in adolescent girls at MAN 2 Karanganyar. Method; This type of research is quantitative with a correlational quantitative research design and through a cross-sectional approach. The sampling technique used Cluster Random Sampling with a population of 379 adolescent girls and a sample of 79 adolescent girls. Data analysis using the Chi-Square test. Results; The results showed that the majority of respondents experienced severe stress as many as 42 (53.16%) with an abnormal menstruation cycle as many as 51 (64.6%). The results of the Chi-Square test obtained a p-value = 0.000, which means that there is a significant relationship between stress levels and the menstruation cycle in adolescent girls of MAN 2 Karanganyar. Conclusion; There is a significant relationship between stress level and menstruation cycle in adolescent girls at MAN 2 Karanganyar.